Development of a decision guide to support the elderly in decision making about location of care: an iterative, user-centered design. Issue 1 (December 2016) - Garvelink, Mirjam; Emond, Julie; Menear, Matthew; Brière, Nathalie; Freitas, Adriana; Boland, Laura; Perez, Maria; Blair, Louisa; Stacey, Dawn; Légaré, France
Plain English summary For the elderly to get the care and services they need, they may need to make the difficult decision about staying in their home or moving to another home. Many other people may be involved in their care too (friends, family and healthcare providers), and can support them in making the decision. We asked informal caregivers of elderly people to help us develop a decision guide to support them and their loved ones in making this decision. This guide will be used by health providers in home care who are trained to help people make decisions. The guide is in French and English. To design and test this decision guide we involved elderly people, their caregivers and health administrators. We first asked them what they needed for making the decision, and then designed a first version of the guide. Then we asked them to look at it and give feedback, which was used to make the final version. We then used scientific criteria to check its content and the language used. The final decision guide was acceptable to the caregivers, their elderly loved ones, and the health administrators. The guide is currently being evaluated in a large research project with home care teams in the province of Quebec. Abstract Background As they grow older, many elderly people are faced with the difficult and preference-sensitive decision about staying in their home or moving to a residence better adapted to their evolving care needs. We aimed to develop an English and French decision aid (DA) for elderly people facing this decision, and to involve end-users in all phases of the development process. Methods A three-cycle design with involvement of end-users in Quebec. End-users were elderly people (n = 4) caregivers of the elderly (n = 5), health administrators involved in home-care service delivery or policy (n = 6) and an interprofessional research team (n = 19).Cycle 1 : Decisional needs assessment and development of the first prototype based on existing tools and input from end-users; overview of reviews examining the impact of location of care on elderly people's health outcomes.Cycle 2 : Usability testing with end-users, adaptation of prototype.Cycle 3 : Refinement of the prototype with a linguist, graphic designer and end-users. The final prototype underwent readability testing and an International Patient Decision Aids (IPDAS) criteria compatibility assessment to verify minimal requirements for decision aids and was tested for usability by the elderly. Results Cycle 1: We used the Ottawa Personal Decision Guide to design a first prototype. As the overview of reviews did not find definitive evidence regarding optimal locations of care for elderly people, we were not able to add evidence-based advantages and disadvantages to the guide.Cycle 2: Overall, the caregivers and health administrators who evaluated the prototype (n = 10) were positive. In response to their suggestions, we deleted some elements (overview of pros, cons, and consequences of the options) that were necessary to qualify the tool as a DA and renamed it a "decision guide".Cycle 3: We developed French and English versions of the guide, readable at a primary school level. The elderly judged the guide as acceptable. Conclusion We developed a decision guide to support elderly people and their caregivers in decision making about location of care. This paper is one of few to report on a fully collaborative approach to decision guide development that involves end-users at every stage (caregivers and health administrators early on, the frail elderly in the final stages). The guide is currently being evaluated in a cluster randomized trial. Trial registration: NCT02244359.